Inisiatif Siswa SMP dalam Merancang Denah melalui STEM - Fatma Salinda; Rahmah Johar; Syahjuzar Syahjuzar (Jurnal Peluang, 2020)
The engagement of students' initiative in designing the floor plan has received less attention from the teacher. Student engagement can be seen from the student's initiative in designing a floor plan during learning. One strategy that can be used is Science, Technology, Engineering, and Mathematics (STEM). STEM integrates science, technology, engineering, and mathematics. This study aimed to describe the students' initiative in designing floor plans through STEM at one of the junior high schools in Banda Aceh, Indonesia. This is descriptive qualitative research. The subjects of this study were seven Year 7 students. Data collection was carried out using observation sheets. Student initiatives in this study were measured by eight indicators: trying to do their job perfectly and seriously, not doing it carelessly, actively participating in discussions, doing more than assigned work, not being communicative, asking questions to get more information, raising hands before responding to questions or expressing opinions, referring to his/her dictionary, encyclopedia, or other references for information, and meeting teachers to discuss learning material before or after school. The results showed that the students' initiative increased in designing floor plans through STEM. This can be seen from students who meet the eight indicators of the initiative. Thus, it can be concluded that all indicators in this study were fulfilled so that students can complete project assignments well.